Tinjauan Fikih Muamalah terhadap Praktik Jual Beli Sapi Bali dengan Sistem Oper Nota di Peternak Sapi Motekar Farm - Ikhsanizar Raihan Firdaus; Nandang Ihwanuddin; Arif Rijal Anshori (Bandung Conference Series: Sharia Economic Law, 2024)
Abstract. Buying and selling is one of the activities that has become popular among mankind and Islam has provided regulations and a basis that is quite clear and firm, one important characteristic that must be practiced in a sale and purchase is honesty because it is very important as a characteristic that will help the human person himself. In addition to the variety of forms of contracts and methods of implementing contracts, in the practice of buying and selling there are also various payment methods. Over time, the problems and models of buying and selling have increased and their implementation is different. One of them is buying and selling using the transfer note system. Motekar Farm carries out buying and selling practices with the transfer note system method, the inconsistency of buying and selling with the transfer note system at Motekar Farm lies in the failure to fulfill the pillars and conditions of the sale and purchase itself. This is an attraction for researchers to research more deeply about the practice of buying and selling with the transfer note system carried out by Motekar Farm and is connected to the Fiqh of Muamalah as a source of law that is the basis for buying and selling practices as a comparison. Then a qualitative method with a descriptive analysis approach was used as a research study, with the aim of comparing the practice of buying and selling that occurred at Motekar Farm with the related Fiqh Muamalah so that it can be concluded that in practice Motekar Farm carries out buying and selling with a note transfer system and this is not in accordance with the concept of buying and selling practices in Fiqh Muamalah which does not fulfill the requirements of the goods being bought and sold. Abstrak. Jual beli merupakan salah satu kegiatan yang telah memasyarakat di kalangan umat manusia dan agama islam telah memberi peraturan dan dasar yang cukup jelas dan tegas, adapun satu sifat yang penting dan harus di praktekkan dalam suatu jual beli adalah kejujuran karena sangat penting sebagai sifat yang akan menolong pribadi manusia itu sendiri. Selain variatifnya bentuk akad dan cara pelaksanaan akad, dalam praktik jual beli juga terdapat macam-macam cara pembayaran. Seiring dengan berjalannya waktu, permasalahan maupun model jual beli semakin banyak dan dalam pelaksanaannyapun berbeda-beda. Salah satunya adalah jual beli dengan menggunakan sistem oper nota. Motekar Farm menjalankan praktik jual beli dengan metode sistem oper nota tersebut, adapun ketidaksesuaian jual beli dengan sistem oper nota di Motekar Farm terletak pada tidak terpenuhinya rukun dan syarat jual beli itu sendiri. Hal ini menjadi daya tarik bagi peneliti untuk meneliti lebih dalam lagi tentang praktik jual beli dengan sistem oper nota yang dilakukan Motekar Farm dan dihubungkan dengan Fikih Muamalah sebagai sumber hukum yang menjadi dasar dari praktik jual beli sebagai perbandingannya. Kemudian digunakanlah metode kualitatif dengan pendekatan deskriptif analisis sebagai kajian penelitiannya, dengan tujuan membandingkan praktik pelaksaan jual beli yang terjadi di Motekar Farm dengan Fikih Muamalah terkait sehingga dapat diambil kesimpulan bahwa dalam Praktiknya Motekar Farm melaksanakan jual beli dengan sistem oper nota dan hal ini tidak sesuai dengan konsep praktik jual beli dalam Fikih Muamalah yang tidak terpenuhinya syarat dari barang yang dijual belikan.